Analisis Ciri Perilaku dan Faktor-Faktor yang Mempengaruhi Proses Belajar Siswa di Madrasah Ibtidaiyah Intisyarul Ulum - khairullina05, Alifia; Sedya Santosa; Vina Tamarin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Research on the relationship between individual behavioral characteristics and factors that influence student learning has become a major focus in the field of psychology. This research uses a descriptive qualitative approach with interview data collection techniques via WhatsApp call. The data obtained was analyzed by condensing data, displaying data, and drawing conclusions. The results of the research show that the application of the insertion method is used to determine various characteristics of children's behavior and what factors influence student learning in madrasa schools. Teachers emphasize a comprehensive literature review regarding the relationship between behavioral traits, such as leadership, motivation, and adaptability, and various types of achievement, including academic achievement, work performance, and achievement in sports contexts.